Gambaran Tingkat Stress Orang Tua Siswa Taman Kanak-Kanak Selama Pembelajaran Daring di Masa Pandemi Covid-19 - Aisyah Azzahra; Muhammad Nanang Suprayogi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
The purpose of the study was to see an overview of the stress levels of parents of students in Kindergarten during online learning during the COVID-19 pandemic. RESEARCH METHODS This research uses a descriptive method with a quantitative approach, using the Perceived Stress Scale (PSS) measuring instrument. Data processing techniques using SPSS. ANALYSIS, obtained as many as 52 respondents consisting of fathers and mothers of students in kindergarten. With the number of male respondents as many as 19 people and female respondents amounted to 33 people. RESULTS ACHIEVED, from this study, it was found that the stress level of parents in kindergarten was at a moderate-stress level with a percentage of 65.4%. CONCLUSION, the percentage of stress levels obtained shows that the stress level of parents who are female is higher than that of the male gender, which may be due to the culture of society where child care is the responsibility of a mother which results in the mother's stress level while accompanying her child to study. from home during the COVID-19 pandemic